Depth‐dependent concentrations of hematopoietic stem cells in the adult skeleton: Implications for active marrow dosimetry. Issue 2 (30th January 2017) - Geyer, Amy M.; Schwarz, Bryan C.; O'Reilly, Shannon E.; Hobbs, Robert F.; Sgouros, George; Bolch, Wesley E.
Abstract : Purpose: The hematopoietically active (or red) bone marrow is the target tissue assigned in skeletal dosimetry models for assessment of stochastic effects (leukemia induction) as well as tissue reactions (marrow toxicity). Active marrow, however, is in reality a surrogate tissue region for specific cell populations, namely the hematopoietic stem and progenitor cells. Present models of active marrow dosimetry implicitly assume that these cells are uniformly localized throughout the marrow spaces of trabecular spongiosa. Data from Watchman et al. and Bourke et al., however, clearly indicate that there is a substantial spatial concentration gradient of these cells with the highest concentrations localized near the bone trabeculae surfaces. The purpose of the present study was thus to explore the dosimetric implications of these spatial gradients on active marrow dosimetry. Methods: Images of several bone sites from a 45‐yr female were retagged to group active marrow voxels into 50 μm increments of marrow depth, after which electron and alpha‐particle depth‐dependent specific absorbed fractions were computed for four source tissues — active marrow, inactive marrow, bone trabeculae volumes, and bone trabeculae surfaces. Corresponding depth‐dependent S values (dose to a target tissue per decay in a source tissue) were computed and further weighted by the relative target cell concentration. These depth‐weighted radionuclide S values were systematically compared to the more traditional volume‐averaged radionuclide S values of the MIRD schema for both individual bones of the skeleton and their skeletal‐averaged quantities. Results: For both beta‐emitters and alpha‐emitters localized in the active and inactive marrow, depth‐weighted S values were shown to differ from volume‐averaged S values by only a few percent, as dose gradients across the marrow tissues are nonexistent. For bone volume and bone surface sources of alpha‐emitters and lower energy beta‐emitters, when marrow dose gradients are expected, explicit consideration of target cell spatial concentration gradients are shown to significantly impact marrow dosimetry. Conclusions: For medical isotopes currently utilized for treatment of skeletal metastases, namely 153 Sm and 223 Ra, accounting for hematopoietic stem and progenitor cell concentration gradients resulted in maximum percent differences to reference skeletal‐averaged S values of ~21% and 55%, respectively.